Microsoft Windows PowerShell 3.0 first look : a quick, succinct guide to the new and exciting features in PowerShell 3.0 /: a quick, succinct guide to the new and exciting features in PowerShell 3.0. (2012) - Driscoll, Adam
No abstract available